2016
DOI: 10.1007/s00246-016-1547-8
|View full text |Cite
|
Sign up to set email alerts
|

HAND1 Loss-of-Function Mutation Causes Tetralogy of Fallot

Abstract: As the most prevalent form of birth defect in humans worldwide, congenital heart disease (CHD) is responsible for substantial morbidity and is still the leading cause of birth defect-related demises. Increasing evidence demonstrates that genetic defects play an important role in the pathogenesis of CHD, and mutations in multiple genes, especially in those coding for cardiac core transcription factors, have been causally linked to various CHDs. Nevertheless, CHD is a genetically heterogeneous disease and the ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 84 publications
0
5
0
Order By: Relevance
“…Minor alleles in the remaining five SNPs (TBX1: rs41298006 G>A, FGF10: rs75629618 C>T, FGF10: rs10461755 G>A, FGF10: rs75632187 A>G, and FGF10: rs12518964 G>A) could only increase the risk of SV. The previous studies focused on SNPs in exons and the promotor regions associated with CHDs (Wang et al, 2014a(Wang et al, , 2017Sun et al, 2016;Huang et al, 2017;Li and Yang, 2017;Li et al, , 2018bLu et al, 2018;Qiao et al, 2018). However, SNPs in introns also play a role in CHD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Minor alleles in the remaining five SNPs (TBX1: rs41298006 G>A, FGF10: rs75629618 C>T, FGF10: rs10461755 G>A, FGF10: rs75632187 A>G, and FGF10: rs12518964 G>A) could only increase the risk of SV. The previous studies focused on SNPs in exons and the promotor regions associated with CHDs (Wang et al, 2014a(Wang et al, , 2017Sun et al, 2016;Huang et al, 2017;Li and Yang, 2017;Li et al, , 2018bLu et al, 2018;Qiao et al, 2018). However, SNPs in introns also play a role in CHD.…”
Section: Discussionmentioning
confidence: 99%
“…The knockout of these genes could lead to different types of CHDs in mice (Dai, 2002;Cai et al, 2003;Dodou, 2004;Phan et al, 2005;Takeuchi, 2005;Vong et al, 2006;Tsuchihashi et al, 2011). Further studies revealed that the mutations in SHF genes played important roles in human CHDs (Huang et al, 2017;Wang et al, 2017;Li et al, 2018a;Xu et al, 2018;Zhang et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, pathogenic mutations of HAND1 were related to left ventricular hypoplasia and ventricular septum defects [ 38 40 ], while HAND2 deficiency contributed to ventricular septum defects and double outlet right ventricle [ 41 ]. In severe CHDs, such as tetralogy of Fallot, mutations of HAND1 / 2 have been identified as well [ 42 , 43 ]. Nevertheless, the roles of HAND in human early cardiac lineage commitment and differentiation are not completely clarified and need further investigation.…”
Section: Introductionmentioning
confidence: 99%
“…Prior work has suggested that the etiology of TOF is multifactorial and associated with chromosomal anomalies such as Trisomies 13, 18, 21, and microdeletion of 22q11.2 (Nguyen & Jay, 2014; Radhakrishna et al, 2018; Vergara et al, 2006). Mutations in certain genes have also been found to be associated with TOF such as JAG1, NKX2‐5, HAND1 , and GATA4 (Bauer et al, 2010; Esposito et al, 2011; Nemer et al, 2006; Wang et al, 2017). These genes encode transcription factors that are important in the regulation of embryologic heart development (Rauch et al, 2010; Vecoli, Pulignani, Foffa, & Andreassi, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…To estimate sample‐to‐sample variability, we compared the degree of dissimilarity between samples of the same tissue type in multiple patients. In addition, we compared gene‐specific DNA methylation profiles across these same tissue types for a representative group of 10 genes previously associated cardiac development: DKK2 (Phillips, Mukhopadhyay, Poscablo, & Westphal, 2011), GATA4 (Garg et al, 2003), HAND1 (Wang et al, 2017), JAG1 (Eldadah et al, 2001), NKX2‐5 (Goldmuntz, Geiger, & Benson, 2001), NOTCH4 (Zhu et al, 2020), SCO2 (Grunert et al, 2016), TBX5 (Sheng et al, 2014), TBX20 (Gong et al, 2019), and WNT7A (Abraham et al, 2022).…”
Section: Introductionmentioning
confidence: 99%